2023
DOI: 10.3389/fcimb.2023.1008783
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of mpox virus using recombinase aided amplification assay

Abstract: A recent, unprecedented outbreak of human mpox virus infection has led to cases in non-African nations, and the number of confirmed or suspected cases outside of Africa has exceeded 1,000 within 5 weeks. Mpox may pose a double threat to public health in the context of the ongoing COVID-19 pandemic. It is difficult to distinguish mpox virus infection from other diseases in the early stages, and patients are contagious from the onset of nonspecific symptoms; therefore, it is crucial to develop rapid and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A different approach was used by Cui et al, who developed a Recombinase-aided amplification (RAA)-based isothermal assay, which would benefit from a significant reduction of analysis time (10 min), costs (5$/sample), and laboratory requirements (i.e. : expertise, cold-chain, RT–PCR instruments); however, a minor analytical sensitivity, compared to RT–PCR, could impair the potential of this technology, especially in a low prevalence context [ 25 ]. The epidemiological scenario extremely changed starting in late 2022, with a highly significant drop in new cases [ 26 ]; nevertheless, the virus continues its circulation under the radar, requiring a new approach: smaller numbers and the need to perform tests in limited expertise settings represent two important issues for surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…A different approach was used by Cui et al, who developed a Recombinase-aided amplification (RAA)-based isothermal assay, which would benefit from a significant reduction of analysis time (10 min), costs (5$/sample), and laboratory requirements (i.e. : expertise, cold-chain, RT–PCR instruments); however, a minor analytical sensitivity, compared to RT–PCR, could impair the potential of this technology, especially in a low prevalence context [ 25 ]. The epidemiological scenario extremely changed starting in late 2022, with a highly significant drop in new cases [ 26 ]; nevertheless, the virus continues its circulation under the radar, requiring a new approach: smaller numbers and the need to perform tests in limited expertise settings represent two important issues for surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the general molecular detection methods, RAA possesses several advantages, such as low-cost, simplicity of operation (as it does not necessitate complex equipment or highly skilled personnel, can be conducted using portable device), low and constant reaction temperature (39°C), and rapid reaction speed (within 20 min) ( Xie et al., 2012 ). As a result, RAA has been widely used in identifying viruses, bacteria, and parasites ( Cui et al., 2022 ; Fu et al., 2022 ; Lin et al., 2022 ; Cui H et al., 2023 ; Cui X et al., 2023 ). Consequently, it represents a rapid and user-friendly method suitable for clinical use, particularly in primary laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on viral and bacterial pathogens have indicated the detection limit of the RAA assay varied from 10 to 142 copies per reaction when tested against standard plasmids ( Zhang et al., 2017 ; Cui et al., 2022 ; Fu et al., 2022 ; Lin et al., 2022 ; Cui H et al., 2023 ; Cui X et al., 2023 ). In this study, a novel and simple method for E. piscicida detection was proposed based on RAA technique.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recombinase-aided amplification (RAA) is a isothermal amplification technology that can complete rapid DNA or RNA amplification at a constant temperature in a short time with accurate results. 19 Here, we developed a RAA assay to detect C. auris, then confirmed its sensitivity, specificity, and application for clinical sample detection, and compared it with real-time PCR to enable timely diagnosis and treatment of C. auris infections and improve patient outcomes. Figure 1C shows the detection mechanism for the RAA assay.…”
Section: ■ Introductionmentioning
confidence: 91%